Aplikasi Pembelajaran Berbasis Multimedia untuk Mata Pelajaran Tematik Tingkat Pendidikan Sekolah Dasar Kelas IV (Studi Kasus: SDIT Al-Kautsar Cikarang) - Veliana Autica; Nuraini Purwandari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
At SDIT Al-Kautsar, the teaching and learning style is still conventional, especially with regard to theme subjects. Learning media are underutilized in the classroom, despite the fact that technology capabilities are available yet underutilized. This research seeks to construct and develop multimedia-based learning apps for fourth grade as thematic learning media. This research applies the Multimedia Development Life Cycle development methodology. Class IV thematic learning applications are produced using Adobe Animate. System testing employing questionnaires and black-box testing methodologies. The blackbox testing of this program revealed that the menu buttons functioned as planned. In addition, the results of the questionnaire indicate that this software is an ideal theme-learning tool for fourth grade. This is clear from the eighty percent average validation rate of principals and thematic teachers.